The Effect of Group Guidance Services to Improve Self-Leadership on the Student Council Administrators - Slamat Fitriyadi; Dian Mayasari; Ahmad Syahroni; Usina Robert Moseki; Wasis Soeprapto (International Journal of Multi Discipline Science, 2022)
This study aims to: (1) Describe the level of students council administrators’ understanding of self-leadership and its application before being given the services. (2) Knowing how much the Group Guidance service influence to improve the student self-leadership in SMA N 1 Singkawang. The research used is quantitative research, with a one-group pretest-posttest design. The population in this study was all the students of council management of SMA N 1 Singkawang, they were 30 students. The study sample was taken purposively with the number of research samples of 9 students. The data collection techniques used in this study were questionnaires, interviews, and documentation, while the data collection instrument in this study used questionnaire guidelines, interview guidelines and documentation in the form of photos of activities. The data analysis technique used Quantitative Percentage Description and Wilcoxon Matched Pairs test analysis. From the results of the percentage description, the results of 3 students were obtained in the high category, 15 students were in the medium category, 8 students were in the less category and 4 students were in a low category. The data were analyzed using the SPSS.25 application. Based on the testing result, it is known that Asymp. Sig. (2-tailed) is worth 0.008. Because the value of 0.008 is smaller than 0.05 (0.008 < 0.05) it can be concluded that H1 is accepted or there is an influence of group guidance services on the self-leadership of the student council management in SMAN 1 Singkawang.